Synergistic Effect of Azotobacter nigricans and Nitrogen Phosphorus Potassium Fertilizer on Agronomic and Yieldtraits of Maize (Zea mays L.) - Sagar, Alka; Sayyed, R. Z.; Ramteke, Pramod W.; Ramakrishna, Wusirika; Poczai, Peter; Al Obaid, Sami; Ansari, Mohammad Javed (Frontiers in Plant Science, 2022)
Among the various biotic and abiotic stress that affect soil and plant health, salinity and heavy metal ion stress are the major threat to nutrient content and crop yield. Among all microorganisms, plant growth-promoting bacteria (PGPB) significantly impact soil's physiological and structural properties. PGPB is an alternative to chemical fertilizers for sustainable agricultural production by stabilizing atmospheric nitrogen and producing growth-promoting substances. Azotobacter sp. is one of the members of the PGPB group, which is an aerobic, free-living, and N2-fixing bacterium that commonly lives in soil, water, and sediments. It plays various beneficial roles by controlling different mechanisms for plant growth. In the present study, salt-tolerant Azotobacter nigricans (KP966496) PR19 was isolated from the organic farm of SHUATS, Allahabad, India. The organism was tolerant to 20% salt and a pH range of 5-9. The organism displayed multiple plant growth-promoting traits such as the production of ammonia (NH3), hydrogen cyanide (HCN), siderophore (SD), indole acetic acid (IAA), 1-aminocyclopropane-1-carboxylate deaminase (ACCD) and phosphate solubilization (PS) activity in addition to tolerance to high levels of trace elements, multiple antibiotics. Under the abiotic stress of salinity and pH, the organism expressed significantly increased (p<0.001) antioxidant enzyme activities (SOD, CAT, and GSH). Inoculation of Different verities of Maize with the A. nigricans showed a significant increase in seed germination and enhancement in elongation of root and shoot compared to untreated control. The combined application of A. nigricans PR19 and NPK treatments showed significant results in all growth and yield parameters of Maize SHIATS-MS-2. This study is the first report on the beneficial effects of organic farm isolated A. nigricans PR19-NPK treatment combinations on sustainable maize productivity.